Zdalna edukacja w perspektywie teorii pola Edukacyjnego Pierre`a Bourdieu. Przypadek uczniów z Europy Środkowo-Wschodniej = Distance education from the perspective of Pierre Bourdieu`s theory of educational field. The case of students from Central and Eastern Europe - Długosz, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to analyse the phenomenon of distance education from the perspective of Pierre Bourdieu`s theory of educational field. Byreferring to the well-known concept of the French sociologist, the author perceives distance education as the performance of actors in the educationalfield, conditioned by the habitus and capitals they possess. The theory used accurately describes and reflects the educational phenomenon that emergedduring the COVID-19 pandemic all over the world.
Keywords: reprodukcja kulturowa; nierówności edukacyjne; pole edukacyjne; edukacja zdalna; pandemia; COVID-19; cultural reproduction theory; educational inequalities; educational field; distance education; pandemic